Biochar Production from Agricultural Wastes via Low-Temperature Microwave Carbonization - Rafeah, Wahi; Sharifah Mona, Abdul Aziz; Sinin, Hamdan; Zainab, Ngaini (IEEE, 2016)
Biochar production from agricultural wastes via low temperature microwave pyrolysis is discussed in the present work as an alternative to the time and energy consuming conventional carbonization. The characteristics of biochar produced from palm kernel shell (PKC), wood chips (WCC) and sago waste (SWC) produced from microwave pyrolysis were investigated. The maximum calorific value of PKC, WCC and SWC in this study was 29.04, 24.89 and 25.99 MJ/kg respectively. FTIR analysis reveals that the biochars contain O-H, C-H and C=C functional groups, while the SEM analysis showed the formation of porous structure of biochars carbonized at lower temperature for all samples. Results indicated the potential use of these biochar as fuel material and precursor for activated carbon.